An evolutionarily conserved gene on human chromosome 5q33-q34,UBH1, encodes a novel deubiquitinating enzyme - Hansen-Hagge, Thomas E.; Janssen, Johannes W. G.; Hameister, Horst; Papa, Feroz R.; Zechner, Ulrich; Seriu, Taku; Jauch, Anna; Becke, Daniela; Hochstrasser, Mark; Bartram, Claus R. (Genomics, 1998)
While cloning breakpoint sequences of a leukemia patient exhibiting a t(5;14) translocation, we identified a pseudogenic variant of a novel multigene family in proximity to the breakpoint. Chromosomalin situhybridization suggested that the gene family is clustered on human chromosome 5q33-q34. The gene family is evolutionarily conserved. Northern blot analysis of mouse tissues revealed low-level expression of a functional member of this gene family in almost all samples. Marked levels of transcripts were detected byin situhybridization in the retina, the olfactory epithelium, the peripheral neuronal ganglia, and distinct areas of the gut. The predicted protein displays striking similarity to a hypothetical protein ofCaenorhabditis elegans(R10E11.3.) and to two yeast deubiquitinating enzymes, Ubp9 and Ubp13, albeit to a lesser extent. We expressed the putative coding region of the human gene inEscherichia coliand demonstrated that it indeed bears deubiquitinating activity based on its ability to cleave ubiquitin from a ubiquitin-β-galactosidase fusion protein. This new deubiquitinating enzyme has been named UBH1, for ubiquitin hydrolyzing enzyme 1.
Elektronische Reproduktion der Druck-Ausgabe 25. Mai 2002
Gesehen am 04.01.2024